Pengaruh Pemberian Coklat terhadap Pengurangan Nyeri Menstruasi Pada Remaja - Nuzulul Husna Ramadhani; Yuyun Triani (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: According to the Indonesian Ministry of Health in 2016, the prevalence of adolescent girls in Indonesia who experienced menstrual pain was around 55% (Susanti, et al, 2018). Based on a preliminary study conducted by researchers on December 5 2022 at MTS Al Mukmin Cemani Grogol Sukoharjo. Information obtained was that 6 out of 10 students said they experienced menstrual pain at the beginning of menstruation as well as feeling lazy to move, weak body and easily felt tired. So from the results of the information obtained, it is necessary to reduce menstrual pain by giving chocolate to find out its effect. Objective: To determine whether there is an effect of giving chocolate on reducing menstrual pain in class VII MTS Al Mukmin Cemani Grogol Sukoharjo. Research method: this research uses a pre-experiment with a one group pretest posttest design. The sample of this research is 20 respondents. Results and discussion: This research uses the Wilcoxon statistical test with a pre-test mean of 3.10 and a post-test mean of 1.10 so that a p-value (asymp.sig 2-tailed) is 0.000 < 0.05, this means H0 is rejected and H1 is accepted. H1 is accepted, meaning there is a significant effect before and after being given chocolate on changes in pain reduction. Conclusion: There is an effect of giving chocolate on reducing the intensity of menstrual pain as proven by the analysis results of p value (0.000) < α value (0.05).